Assessment of benthic and coral community structure in an inshore reef in Balok, Pahang, Malaysia - MUHAMMAD FAIZ MOHD HANAPIAH; SHAHBUDIN SAAD; ZUHAIRI AHMAD; MUHAMMAD HAMIZAN YUSOF; MOHD FIKRI AKMAL KHODZORI (Society for Indonesian Biodiversity, 2019)
Abstract. Hanapiah MFM, Saad S, Ahmad Z, Yusof MH, Khodzori MFA. Assessment of benthic and coral community structure in an inshore reef in Balok, Pahang, Malaysia. Biodiversitas 20: 872-877. Inshore water reef closer to human activities are often neglected since they are not protected by marine park management. Little is known on how this reef responses to challenging environment in terms of abundance, diversity and benthic community composition. This study provides a quantitative assessment on the benthic community composition at 5 reef sites in Balok, Pahang, Malaysia and observed the ecological adaptation in the reef community towards turbid water environment. Balok reef has 39% overall coral cover with very low macroalgae abundance (4%). A total of 28 coral genera from 12 families have been recorded with Porites the most dominant genus in the coral assemblages. Most reef sites in Balok are categorized under conservation class 1 (CC1), which indicated that resilient and survival of the reef rely on stress-tolerators taxa. The data presented here showed that Balok reef is highly resilient towards constant exposure to high sedimentation and wave action.